LABORATORY INVESTIGATION OF THE USE OF CRUSHED OYSTER SHELL AND CRUSHED PALM-KERNEL SHELL IN BITUMINOUS MIX DESIGN (Malaysian Journal of Civil Engineering, 2018)
The potentials use of crushed oyster shell (COS) and crushed palm kernel shell (CPKS) as partial replacement of fine aggregates in bituminous surfacing were investigated. Fine aggregate was partially replaced with COS and CPKS in proportions of 0%, 10%, 20%, 30%, 40% and 50% by weight of varying bitumen content from 3% to 9.5%. Marshall Stability tests were carried out in accordance with American Standard for Materials and Testing (ASTM D 1559: 2004). 30% partial replacement was within the specifications for bituminous surfacing, having 6% optimum bitumen content. The Marshal Stability obtained with COS and CPKS was 2.70 kN and 2.31 kN respectively; the corresponding flow value was 4.10 mm, and 4.15 mm. Thus, partial replacement of fine aggregate with 30% COS and CPKS in bituminous mix is suitable for light traffic and can be used as alternative material in bituminous mix to reduce the cost of construction.